An Integrated Analysis of the Identified PRPF19 as an Onco-immunological Biomarker Encompassing the Tumor Microenvironment, Disease Progression, and Prognoses in Hepatocellular Carcinoma - Yang, Ming; Qiu, Yiwen; Yang, Yi; Wang, Wentao (Frontiers in Cell and Developmental Biology, 2022)
Background: Targeting the mRNA splicing process has been identified as a therapeutic strategy for human cancer. PRPF19 is an RNA binding protein that is involved in pre-mRNA processing and repairing DNA damage, the aberrant expression of PRPF19 is potentially associated with carcinogenesis. However, the biological role of PRPF19 in hepatocellular carcinoma (HCC) is still elusive. Methods: Data obtained from TCGA, Oncomine, and GEO were used to investigate the PRPF19 expression level and its role in tumor immune infiltration, prognosis, the tumor progression of cohorts from HCC. Using various databases and tools (UALCAN, TIMER, TISMO, and PathCards), we presented the potential mechanisms of PFPF19 upregulation, PRPF19-related pathways, and its biological functions in liver cancer. Results: For HCC, PRPF19 expression was found up-regulated both in single tumor cells and tissues. Further, the increased expression of PRPF19 was significantly correlated to clinical characteristics: advanced stage, vascular invasion, high AFP, and poor prognosis of HCC. According to the tumor-immunological analysis, we found that PRPF19 is positively correlated with infiltrating Myeloid-derived suppressor cells (MDSCs). Moreover, the microenvironment of HCC tissues with high expression PRPF19 is highly immunosuppressive (lower t lymphocytes, multiple immune checkpoints up-regulated). Patients with high expression of PRPF19 and high MDSCs had a worse survival prognosis as well. TP53 mutated may have a positive effect on PRPF19 expression via decreased promoter methylation of PRPF19. By TF-mRNA network analysis, key transcription factors (TFs) in TC-NER and PCS pathways (PRPF19 involved) were identified. Conclusion: This work implied that PRPF19 is associated with tumor immune evasion, progression and serves as a prognostic marker for worse clinical outcomes with HCC. Thus, this critical regulator could serve as a potential therapeutic target of HCC.